Implementing a Telehospitalist Program Between Veterans Health Administration Hospitals: Outcomes, Acceptance, and Barriers to Implementation. Issue 3 (17th February 2021) - Gutierrez, Jeydith; Moeckli, Jane; Holcombe, Andrea; O'Shea, Amy MJ; Bailey, George; Rewerts, Kelby; Hagiwara, Mariko; Sullivan, Steven; Simon, Melissa; Kaboli, Peter
Abstract : BACKGROUND: Telehospitalist services are an innovative alternative approach to address staffing issues in rural and small hospitals. OBJECTIVE: To determine clinical outcomes and staff and patient satisfaction with a novel telehospitalist program among Veterans Health Administration (VHA) hospitals. DESIGN, SETTING, AND PARTICIPANTS: We conducted a mixed‐methods evaluation of a quality improvement program with pre‐ and postimplementation measures. The hub site was a tertiary (high‐complexity) VHA hospital, and the spoke site was a 10‐bed inpatient medical unit at a rural (low‐complexity) VHA hospital. All patients admitted during the study period were assigned to the spoke site. INTERVENTION: Real‐time videoconferencing was used to connect a remote hospitalist physician with an on‐site advanced practice provider and patients. Encounters were documented in the electronic health record. MAIN OUTCOMES: Process measures included workload, patient encounters, and daily census. Outcome measures included length of stay (LOS), readmission rate, mortality, and satisfaction of providers, staff, and patients. Surveys measured satisfaction. Qualitative analysis included unstructured and semi‐structured interviews with spoke‐site staff. RESULTS: Telehospitalist program implementation led to a significant reduction in LOS (3.0 [SD, 0.7] days vs 2.3 [SD, 0.3] days). The readmission rate was slightly higher in the telehospitalist group, with no change in mortality rate. Satisfaction among teleproviders was very high. Hub staff perceived the service as valuable, though satisfaction with the program was mixed. Technology and communication challenges were identified, but patient satisfaction remained mostly unchanged. CONCLUSION: Telehospitalist programs are a feasible and safe way to provide inpatient coverage and address rural hospital staffing needs. Ensuring adequate technological quality and addressing staff concerns in a timely manner can enhance program performance. Abstract :